KONTRASTIF FONEM TUNGGAL BAHASA INDONESIA DAN MANDARIN (Sebuah Studi Analisis Kontrastif Bahasa) - Alexandra Sawitri Ekapartiwi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
When learning a foreign language or second languagelearning (L2) for native language users (L1), there are somedifferences which learners cannot avoid. Several factors underlie thatproblem. Chinese learners in Indonesia also experience the problem.Pinyin spelling system is quite different from Indonesian spellingsystem and it causes some distinctions in L1 and L2. ContrastiveAnalysis approach (henceforth anakon) can be the answer to solve theproblem. A subordinate study by Carl James discusses two maindifficulties in phonology and structure. Anakon can be understood byoutlining the meaning of L1 and L2 words. By using anakon, thedifferences between L1 and L2 will get clearer.